A pillar-layered binuclear 3D cobalt(ii) coordination polymer as an electrocatalyst for overall water splitting and as a chemosensor for Cr(vi) anion detection. Issue 36 (17th August 2021) - Zhao, Dongsheng; Song, Junqi; Zhang, Xiutang; Wang, Feng; Li, Bei; Yang, Lulu; Deng, Yuxin; Li, Qingbo; Fan, Liming
Abstract : A 3D pillar-layered cobalt(ii ) CP with a 3D (4, 6)-connected {4 4 ·6 10 ·8}{4 4 ·6 2 } fsc net was designed and it showed great potential as an electrocatalyst in the overall water splitting and as a chemosensor for Cr(vi ) anion detection. Abstract : Based on binuclear {Co2 (COO)4 } SBUs, a pillar-layered 3D (4, 6)-connected {4 4 ·6 10 ·8}{4 4 ·6 2 } fsc net, was constructed via a mixed ligand strategy. Electrocatalytic research showed that the 1 @NF electrode shows better OER performance than RuO2 @NF, reaching a current density of 10 mA cm −2 when the overpotential of OER is was 370 mV in a 1.0 M KOH electrolyte, with a Tafel slope of 15.6 mV dec −1 . Moreover, the overpotential of HER of 246 mV at a current density of 10 mA cm −2, with a Tafel slope of 23.1 mV dec −1, also suggested that the HER performance of 1 @NF is better than that of Pt/C@NF. The durability test manifested that the electrocatalytic activity of 1 @NF can be maintained at 92.8% after 12 h in 1.0 M KOH. Besides, luminescence sensing experiments reveal that 1 is an efficient chemosensor, which exhibits high sensitivity, high selectivity, and good recyclability towards the detection of Cr(vi ) anions in water even in the presence of other interfering anions. The detection limits are as low as 3.42 × 10 −6 M for the CrO4 2− anion and 2.96 × 10 −7 M for the Cr2 O7 2− anion. The electrocatalytic and luminescence sensing properties show that 1 is an excellent candidate for multifunctional materials in energy conversion and pollutant detection.